2015
DOI: 10.1007/s00702-015-1408-2
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression of dopamine receptors in peripheral blood lymphocytes of computer game addicts

Abstract: Excessive playing of computer games like some other behaviors could lead to addiction. Addictive behaviors may induce their reinforcing effects through stimulation of the brain dopaminergic mesolimbic pathway. The status of dopamine receptors in the brain may be parallel to their homologous receptors in peripheral blood lymphocytes (PBLs). Here, we have investigated the mRNA expression of dopamine D3, D4 and D5 receptors in PBLs of computer game addicts (n = 20) in comparison to normal subjects (n = 20), using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Leeman and Potenza, Griffiths et al., Ong et al., Vousooghi et al. ), multiple similarities have been described between addictive gaming and other addictions such as substance dependency or pathological gambling. For example, Fauth‐Bühler and Mann found loss of sensitivity, increased reactivity to related cues, increased impulsivity, and altered reward‐based learning in addictive gamers and pathological gamblers compared with healthy individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leeman and Potenza, Griffiths et al., Ong et al., Vousooghi et al. ), multiple similarities have been described between addictive gaming and other addictions such as substance dependency or pathological gambling. For example, Fauth‐Bühler and Mann found loss of sensitivity, increased reactivity to related cues, increased impulsivity, and altered reward‐based learning in addictive gamers and pathological gamblers compared with healthy individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have suggested an association between IGD and a dysfunction of the dopaminergic system . Vousooghi et al . found a reduced number of D5 dopamine receptors in computer game addicts compared with healthy individuals.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a chronic rise in D1R might be a risk factor that predisposes individuals to some type of addiction allowing one to diagnose the severity of the addictive condition [ 281 ]. The expression of DA receptors in the immune system might be a valuable biomarker of the risk for pathologies and addictive conducts; thus, it has also been measured in computer game addicts, in whom DRD5 levels in circulating lymphocytes are lower than in control subjects [ 137 ]. Notably, the personality of volunteers has been correlated with the expression of the DRD3 and DRD4 receptors [ 282 ].…”
Section: Clinical Implications Of the Effects On The Dopaminergic mentioning
confidence: 99%
“…The involvement of dopamine appears to differ in non-trivial ways between gaming and substance abuse (e.g. Vousooghi et al, 2015). Similarly, we urge caution in assuming that gaming works similarly to gambling.…”
Section: Distancing Pg From Substance Abuse and Gamblingmentioning
confidence: 91%